Methods and parameters of melting curve analysis for identification of Leishmania species: A scoping review - Juliana J G Ferreira; Fernanda S Nascimento; Gláucia E B Marcon; Eros A de Almeida; Sandra C B Costa (Asian Pacific Journal of Tropical Medicine, 2021)
Leishmaniasis is a set of diseases with a worldwide distribution that affects mainly economically underprivileged populations in developing countries. It has a major impact on public health, with a global cost of billions of dollars per year. The treatment and control of leishmaniasis vary according to the Leishmania species involved, which require reliable methods for species identification. Since most of the currently used methods have limitations, there is a need for assays that allow rapid, precise identification of the offending species. Real-time polymerase chain reactions in conjunction with dissociation curve analysis have been used to detect differences in the DNA composition of selected genes of Leishmania spp. Kinetoplast DNA is the main molecular target used because of its high copy number per parasite, but other targets have also been studied. As part of an effort to establish melting temperature standards for each target gene, we have reviewed the pertinent literature available in public databases, including PubMed, Web of Science, SciELO and LILACS, using the keywords “Leishmania”, “leishmaniasis”, “real-time PCR”, “melting temperature”, and “melting curve”, alone or in combination. After applying eligibility criteria, 27 articles were selected for analysis. A considerable variation in the methodologies analyzed was found regarding molecular targets, standardization of the methods, reproducibility and specificity. Because of this, statistical analysis was not performed. In most cases, the methods were able to differentiate the parasite at the subgenus level or few species regardless of the target chosen.